Kingdom of the planet of the apes [videorecording (Blu-Ray)] - Jaffa, Rick; Silver, Amanda (20th Century Studios, 2024)
"Generations in the future following Caesar's reign, apes are living harmoniously as the dominant species -- and humans are living in the shadows. As a new tyrannical ape leader builds his empire, one young ape undertakes a harrowing journey that will cause him to question the past and make choices that will define a future for apes and humans alike" --Container.